CAR SALES PREDICTION ANALYSIS WITH COMPUTER BASED THETA METHOD - Djunaidy Santoso (Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
The economic development in Indonesia is growing rapidly, competition is increasing. One of the things that are important in supporting the success of a company is to be able to meet the demands of various consumers. Activities that enable us to predict what will happen in the future are known as forecasting.Forecasting Theta methods, by Assimakopoulos Theta and Nikolopoulos. Initially, forecasting only use 2 theta weights parameters, then another theta parameter is added. Currently the Theta method use theta weight parameter. This research is to perform sales forecasting on car sales using Theta Method with five different weights using a system specially designed to perform the calculation. The error is minimized by minimizing the Mean Squared Error (MSE).Â As a result, using Theta weight 3 produces the smallest error.Â Keywords: Theta method, forecasting, timeseries, Mean Squared Error